2021
DOI: 10.1051/e3sconf/202131702027
|View full text |Cite
|
Sign up to set email alerts
|

Politeness in the Use of Language in Social Media

Abstract: The use of social media in communication changes the way people express the idea represented through their language. This study aims to seek for the form of communication patterns in social media and to reveal causes of specific pattern language usage found in media, especially in office domain. The study was conducted using descriptive qualitative by describing the results of observations, interviews, and documentation. The data were collected by non-participatory observation method and note taking technique.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…A computer-mediated technology that makes it easier to create and share information, ideas, and other kinds of expression through virtual communities or networks is what experts define as social media. We can see the different social media platforms by the services offered, which include those for collaboration, communication, and multimedia (Chandra, 2021). Social media offers a wide range of services that have an influence on how its users communicate by introducing new linguistic forms as a contemporary communication medium.…”
Section: Introductionmentioning
confidence: 99%
“…A computer-mediated technology that makes it easier to create and share information, ideas, and other kinds of expression through virtual communities or networks is what experts define as social media. We can see the different social media platforms by the services offered, which include those for collaboration, communication, and multimedia (Chandra, 2021). Social media offers a wide range of services that have an influence on how its users communicate by introducing new linguistic forms as a contemporary communication medium.…”
Section: Introductionmentioning
confidence: 99%
“…Social media is an internet-based platform that enables users to interact by sharing text, images, videos, and audio. Nowadays, social media is considered the most effective means of communication because, with an internet connection, anyone can connect and interact with others anytime and anywhere (Chandra, 2021). According to Datareportal, based on a survey conducted by Kepios, it was found that as of October 2022, 59.3 percent of the world's total population, or approximately 4.74 billion people, are social media users.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have researched and found various cases of it. For example, the WhatsApp application's conversation among lecturers and administrative staff used most utterances to represent obedience to the politeness maxim (Chandra, 2021). The people interacting on the WHO Instagram's official account used four politeness strategies in their utterances (Mulyana, 2021).…”
Section: A Introductionmentioning
confidence: 99%